Translation Review of Cultural Specific Terms in the Book Entitled “Ajaran Kepemimpinan Asthabrata Kadipaten Pakualaman” - Sri Marwati; Dimas Adika; Widyasari (PRAGMATICA : Journal of Linguistics and Literature, 2026)
The objective of this research is to analyze the translation strategy of cultural terms in the book Ajaran Kepemimpinan Asthabrata Kadipaten Pakualaman by K.G.P.A.A Paku Alam X. This book discusses leadership values in Javanese culture. This research employs a qualitative desciptive method, adopts a textual analysis approach focusing on the analysis of cultural terms and their translations in the english version. The analysis applies Peter Newmark’s theory of semantic translation to examine how meaning and cultural nuances are preseverd or shifted. This research is adopted the theoretical of Lawrence Venuti’ foreignisation strategy is use to evaluate how cultural elements and uniqueness are maintained in the target languages.The results of the research indicate that the translation of cultural terms in the book use communicative and domestication translation strategies.The contribution of the translation is the symbolic and philosophical richness of Javanese culture.This research found that the importance of a balance between the accuracy of meaning and cultural preservation in cross-language and cross-cultural translations.